Mothers' perception of neonatal jaundice in Lagos, Nigeria: An urgent need for greater awareness - Chinyere Ezeaka; Ekanem Ekure; Iretiola Fajolu; Beatrice Ezenwa; Patricia Akintan (South African Medical Association, 2016)
Background. Neonatal jaundice remains a leading cause of preventable brain damage, mental handicap, physical disabilities and early death among infants. The high mortality and morbidity from neonatal jaundice is exacerbated by the poor understanding and mismanagement of this common neonatal problem by the general populace, leading to dangerous delays and complications. Objective. To assess the knowledge of pregnant women on the causative factors, treatment modalities and sequelae of neonatal jaundice. Methods. Data were obtained from all consecutive women who attended the antenatal clinic of the Lagos University Teaching Hospital, Nigeria, from January 2013 to April 2013, using a pretested questionnaire focusing on knowledge of neonatal jaundice and its causes, treatment and complications. Results. The study participants numbered 395, of whom 213 (53.9%) were within the age range of 30 - 39 years. Only 101 (25.6%) participants gave a correct definition of neonatal jaundice. The highest proportion of those who did not give a correct definition were from the lower socioeconomic groups V and IV (χ2=12.08, p=0.017). Participants who did not know the causes numbered 313 (79.2%), while 325 (82.2%) participants chose ineffective treatment options. Furthermore, 296 (74.9%) respondents, especially those with a low level of education, did not identify the complications correctly (χ2=12.61, p=0.006). Conclusion. Women in the study showed inadequate knowledge of and misconceptions regarding neonatal jaundice, which must be addressed in order to reduce significantly the devastating consequences of this common condition. We advocate for improved female literacy and mass health enlightenment programmes.